New ophthalmic drug delivery systems - Ana Castro-Balado; Cristina Mondelo-García; Irene Zarra-Ferro; Anxo Fernández-Ferreiro (Farmacia Hospitalaria)
For decades, topical ophthalmic drug administration through the use of eye drops has been the most widely used technique for the treatment of eye diseases. The development of galenic formulation has led to the use and commercialization of new formulations, such as suspensions, emulsions, and ophthalmic ointments that increase residence time in the site of action. Recently, new administration systems have been developed, such as devices and inserts that provide the sustained release of active substance. Some of these systems are already available on the market, whereas others are still undergoing clinical trials, such as promising systems based on nanostructures (nanocapsules, cyclodextrins, nanoemulsions, etc.). Similarly, various formulations and devices have been developed in the field of intravitreal administration, with different implants available on the European market for the treatment of age-related macular degeneration (AMD), diabetic macular edema, or infections that affect the posterior segment. This review includes current developments in ophthalmic topical and intravitreal drug administration routes as well as those under investigation.